Bone Fracture Toughness and Strength Correlate With Collagen Cross‐Link Maturity in a Dose‐Controlled Lathyrism Mouse Model. (16th February 2015) - McNerny, Erin MB; Gong, Bo; Morris, Michael D; Kohn, David H
ABSTRACT: Collagen cross‐linking is altered in many diseases of bone, and enzymatic collagen cross‐links are important to bone quality, as evidenced by losses of strength after lysyl oxidase inhibition (lathyrism). We hypothesized that cross‐links also contribute directly to bone fracture toughness. A mouse model of lathyrism using subcutaneous injection of up to 500 mg/kg β‐aminopropionitrile (BAPN) was developed and characterized (60 animals across 4 dosage groups). Three weeks of 150 or 350 mg/kg BAPN treatment in young, growing mice significantly reduced cortical bone fracture toughness, strength, and pyridinoline cross‐link content. Ratios reflecting relative cross‐link maturity were positive regressors of fracture toughness (HP/[DHLNL + HLNL] r 2 = 0.208, p < 0.05; [HP + LP]/[DHNL + HLNL] r 2 = 0.196, p < 0.1), whereas quantities of mature pyridinoline cross‐links were significant positive regressors of tissue strength (lysyl pyridinoline r 2 = 0.159, p = 0.014; hydroxylysyl pyridinoline r 2 = 0.112, p < 0.05). Immature and pyrrole cross‐links, which were not significantly reduced by BAPN, did not correlate with mechanical properties. The effect of BAPN treatment on mechanical properties was dose specific, with the greatest impact found at the intermediate (350 mg/kg) dose. Calcein labeling was used to define locations of new bone formation, allowing for the identification of regions of normally cross‐linked (preexisting) and BAPN‐treated (newly formed, cross‐link‐deficient) bone. Raman spectroscopy revealed spatial differences attributable to relative tissue age and effects of cross‐link inhibition. Newly deposited tissues had lower mineral/matrix, carbonate/phosphate, and Amide I cross‐link (matrix maturity) ratios compared with preexisting tissues. BAPN treatment did not affect mineral measures but significantly increased the cross‐link (matrix maturity) ratio compared with newly formed control tissue. Our study reveals that spatially localized effects of short‐term BAPN cross‐link inhibition can alter the whole‐bone collagen cross‐link profile to a measureable degree, and this cross‐link profile correlates with bone fracture toughness and strength. Thus, cross‐link profile perturbations associated with bone disease may provide insight into bone mechanical quality and fracture risk. © 2014 American Society for Bone and Mineral Research.